Estrategias de Afrontamiento que usan los profesionales de enfermeria para evitar el sindrome de Burnout - Medina-Almeyda, Rosa-Marisella (2022)
Objectives: To determine the coping strategy applied by nurses to avoid Burnout syndrome in the 5th and 6th East Surgery Services of the National Institute of Neoplastic Diseases. Methodology: This was a quantitative, descriptive, non-experimental, cross-sectional study. The population consisted of 50 nursing professionals. The cope questionnaire was used to identify coping strategies. The results showed that the majority of nurses used: coping focused on the problem, followed by emotion and the lowest percentage was focused on cognitive avoidance. It is concluded that nurses in their work environment must constantly use strategies that allow them to avoid emotional exhaustion. Likewise, soft skills training, as well as self-care activities are preventive actions that allow them to feel well.